2018
DOI: 10.1111/jne.12655
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter differences associated with age and sex hormone levels between premenopausal and perimenopausal women: A voxel‐based morphometry study

Abstract: The present study aimed to explore brain morphological alterations associated with age and sex hormone levels between premenopausal and perimenopausal women using magnetic resonance imaging (MRI) T1‐weighted structural images. Thirty‐two premenopausal women aged (mean ± SD) 47.75 ± 1.55 years and twenty‐five recently perimenopausal women aged 51.60 ± 1.63 years were evaluated for sex hormone levels, including prolactin, follicle‐stimulating hormone, luteinising hormone, oestradiol, free testosterone and proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
(193 reference statements)
2
24
0
Order By: Relevance
“…The present finding might give potential explanation for depression in women during menopause transition. In addition, a previous voxel-based morphometry study by our group has found that perimenopausal women showed decreased gray matter volume in the right SFG compared with premenopausal women (10). There is a close relationship between structure and function of the human brain (32).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The present finding might give potential explanation for depression in women during menopause transition. In addition, a previous voxel-based morphometry study by our group has found that perimenopausal women showed decreased gray matter volume in the right SFG compared with premenopausal women (10). There is a close relationship between structure and function of the human brain (32).…”
Section: Discussionmentioning
confidence: 70%
“…In the recent decade, neuroimaging techniques have been applied to investigate alterations of the brain in women during menopause transition (1,10,(12)(13)(14). Functional magnetic resonance imaging (fMRI), as a popular tool in neuroscience, has been used to study brain functional changes in women during menopause transition (1,12).…”
Section: Introductionmentioning
confidence: 99%
“…More studies are needed to further investigate the mechanisms. With regard to the relationship between the FSH level and gray matter, previous study showed that the gray matter volume of the right inferior parietal gyrus was decreased in perimenopausal women than premenopausal women ( 41 ). As we all know, the serum FSH level in perimenopausal women was obviously increased than in premenopausal.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal cortex and posterior cingulate cortex showed consistent biomarker abnormalities in peri- and postmenopausal women [ 6 ]. Lu et al found that the gray matter volume in multiple brain regions of perimenopausal women decreased [ 7 ]. However, previous studies of perimenopausal women mainly focused on the changes in brain structure and morphology, not yet revealed the overall changes in the spontaneous activity of whole brain,which did not point out abnormal area of the brain accurately.…”
Section: Introductionmentioning
confidence: 99%